Ciclopirox inhibits SARS-CoV-2 replication by promoting the degradation of the nucleocapsid protein - Xiafei Wei; Yuzheng Zhou; Xiaotong Shen; Lujie Fan; Donglan Liu; Xiang Gao; Jian Zhou; Yezi Wu; Yunfei Li; Wei Feng; Zheng Zhang (Elsevier, 2024)
The nucleocapsid protein (NP) plays a crucial role in SARS-CoV-2 replication and is the most abundant structural protein with a long half-life. Despite its vital role in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) assembly and host inflammatory response, it remains an unexplored target for drug development. In this study, we identified a small-molecule compound (ciclopirox) that promotes NP degradation using an FDA-approved library and a drug-screening cell model. Ciclopirox significantly inhibited SARS-CoV-2 replication both in vitro and in vivo by inducing NP degradation. Ciclopirox induced abnormal NP aggregation through indirect interaction, leading to the formation of condensates with higher viscosity and lower mobility. These condensates were subsequently degraded via the autophagy-lysosomal pathway, ultimately resulting in a shortened NP half-life and reduced NP expression. Our results suggest that NP is a potential drug target, and that ciclopirox holds substantial promise for further development to combat SARS-CoV-2 replication.